(untitled) (Journal of Small Business Strategy (archive only), 2018)
Entrepreneurial marketing is a useful entrepreneurial strategy to achieve certain goals. This is mostly true for nascent entrepreneurs running small businesses for two main reasons. On the one hand, these entrepreneurs encounter various kinds of resource scarcity. On the other hand, nascent entrepreneurs, especially the ones without having any previous start-up experience, face decision complexity and decision uncertainty in their decisions, including marketing decisions. Given the fact that entrepreneurial marketing emanates from entrepreneurial thinking and decision-making, there should be a direct link between entrepreneurial marketing and entrepreneurial decision-making. Coming to the conclusion that there are few, if any, studies regarding entrepreneurial decisions in entrepreneurial marketing, we conducted a qualitative content analysis to present a taxonomy of main entrepreneurial marketing decisions. According to our findings based on the data gathered by conducting semi-structured interviews with nascent Iranian high-tech entrepreneurs active in biotechnology and nanotechnology industries and analyzed by open coding, marketing mix decisions, core marketing decisions, market entry decisions, opportunity-related decisions, innovation decisions as well as growth decisions are the main decisions made by nascent entrepreneurs, respectively.